Governor of the Cordillera John C. Early among the Philippine highlanders - Woods, L. Shelton (NIU series in Southeast Asian Studies.)
"Combining biography with colonial history, this book uncovers the secret history of America's treatment of the 300,000 highlanders who lived in Luzon as well as the life of John Early, who served as governor in the region and was a defender of the rights of the Igorots"